Consolidated report on agroecological codesign of innovations in India - Kumar, Gopal; Malaiappan, Sudharsan; Triomphe, B.; Shamim, Md.; Gadewar, P.; Acharya, S.; Samaddar, A.; Borah, Gulshan; Sikka, Alok; Monserrate, F.; Singh, Sonali; Krishnan, S. (International Water Management Institute, 2024)
This report consolidates insights from the co-design of agroecological innovations under the Agroecology Initiative in India, focusing on Mandla and Andhra Pradesh Agroecological Living Landscape (ALL). The participatory approach engaged diverse stakeholders, particularly women farmers, to address challenges such as poor production and agrobiodiversity, degraded soils, water scarcity, and livelihood insecurity. Key interventions included Agroecological Homestead Models (AHMs), Krishi-Kund for land restoration, Solar Irrigation Systems based diversified farming, Integrated Farming Systems (IFS), Integrated Rice-Fish Farming, and homeopathic formulations for crop improvement.